PROTOTIPE APLIKASI PENGENALAN WAYANG KULIT MENGGUNAKAN CNN BERBASIS VGG16 - prabowo, dwi puji; Ullumudin, D.I.I; Pramunendar, R.A. (Universitas PGRI Semarang, 2021)
Indonesia has various types of culture and traditional arts. In this era of globalization, local culture and arts have begun to be eroded by the times. One of the diverse Indonesian culture is wayang kulit. Where the shadow puppets in Indonesia vary and vary from region to region. In this case, the puppet characters have different forms and curves, so recognizing the shape of a puppet is very difficult. In the development of technology, computer vision technology began to be widely used to perform object recognition with deep learning learning. So that an object being studied can be detected properly. In this study, a prototype was made with the detection of puppet types using Deep Learning learning using Convolutional Neural Networks to detect shadow puppet objects based on the VGG16 architecture. The results obtained by the CNN and VGG16 methods reached 86%. With the results obtained, a prototype model is made which will later be able to help the community in the introduction of shadow puppets.Keyword: CNN, shadow puppets ,VGG16